278 Fleece and fiber characteristics of Rambouillet, Targhee, and their reciprocal-crosses at first shearing. (30th November 2020) - Murphy, Tom; Stewart, Whit C; Notter, Dave; Knuth, Ryan; Feagler, Trestin; Taylor, Bret
Abstract: Objectives were to evaluate breed, heterosis (HI ), and maternal effects on wool production in Rambouillet (R x R), Targhee (T x T), and reciprocal-cross (R x T and T x R) 1-yr-old ewes. Greasy fleece weights (GFW) were obtained at shearing and mid-side, britch, and whole-fleece core wool samples were collected to quantify average (A-FD) and CV of fiber diameter (CV-FD). Laboratory scoured yield (LSY) was quantified on core samples and used to estimate clean fleece weight (CFW). Single-born ewes had greater GFW (3.48 kg), greater CFW (2.11 kg), and lower mid-side CV-FD (17.5%) than multiple-born ewes (3.18 kg, 1.95 kg, and 18.1%, respectively; P < 0.01). Rambouillet-sired ewes had greater LSY than T-sired ewes (60.6 vs. 60.0%; P < 0.01), but no breed effects were detected for GFW or CFW. A sire breed x dam breed interaction effect was detected for A-FD at all locations (P ≤ 0.05). Reciprocal-cross performance indicated unfavorable HI for A-FD within mid-side (+0.34 μm), britch (+0.97 μm), and core samples (+0.42 μm; P ≤ 0.05) compared to purebred average. Greater mid-side and britch A-FD in R x T (22.8 and 25.2 μm) than T x R ewes (21.2 and 23.5 μm; P < 0.01) implied a more favorable additive maternal effect for crossbred ewes gestated and reared by R compared to T dams. Future analyses will consider lifetime lamb and wool production of these breed types to evaluate the utility of finewool crossbred ewes in extensive production systems.